PENGARUH PERCEPTUAL MOTOR TRAINING TERHADAP KESEIMBANGAN DINAMIS PADA ANAK AUTISM SPECTRUM DISORDER - Ansari, Nabila Vinca; Hariandja, Andy Martahan Andreas; Pambudi, Restu Arya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Introduction: One of the perceptual and motor disorders in Austim Spectrum Disorder (ASD) children is dynamic balance. Dynamic balance disorders can be seen from the inability of children to maintain certain positions such as walking, jumping, and unstable running. The purpose of this study was to determine the effect of Perceptual Motor Training (PMT) on dynamic balance in ASD children. Methods: This type of research is pre-experimental with one group pre-test post-test design. The sample size was 12 ASD children who met the inclusion and exclusion criteria. Exercise was given three times a week for four weeks. Dynamic balance measurements using the modified bass test of dynamic balance. Hypothesis testing of bivariate analysis using paired sample t-test. Results: The statistical test results between before and after the intervention on dynamic balance get a p-value of 0.000 (<0.05) means there is an influence. Conclusion: There is an effect of Perceptual Motor Training on dynamic balance in Autism Spectrum Disorder children.